Zebrafish in dermatology: a comprehensive review of their role in investigating abnormal skin pigmentation mechanisms - Qu, Junying; Yan, Mengjun; Fang, Yimeng; Zhao, Jing; Xu, Ting; Liu, Fan; Zhang, Kun; He, Luqing; Jin, Libo; Sun, Da (Frontiers in Physiology, 2023)
Skin pigmentation abnormalities, ranging from aesthetic concerns to severe hyperpigmentation disease, have profound implications for individuals’ psychological and economic wellbeing. The intricate etiology of hyperpigmentation and our evolving comprehension of its underlying mechanisms underscore the need for robust animal models. Zebrafish, renowned for their transparent embryos and genetic parallels to humans, have been spotlighted as a pivotal model for skin pigmentation studies. This review offers a concise overview of zebrafish skin attributes, highlighting the shared melanin production pathways with humans. We systematically dissect the diverse strategies to craft zebrafish models of abnormal skin pigmentation, spanning physical, chemical, and genetic interventions, while critically appraising the merits and constraints of each approach. Additionally, we elucidate the metrics employed to gauge the efficacy of these models. Concluding, we cast a visionary gaze on prospective breakthroughs in the domain, aiming to steer forthcoming efforts in refined zebrafish models for skin pigmentation research.